Knight watch - Akers, Tim, 1972- (Baen, 2021)
"John Rast went to the Ren Faire looking for a fight. Well, a simulated fight, with blunt swords and safety equipment. But when his final opponent turns into a living, fire-breathing dragon, John finds himself in the fight of his life. And that's when destiny comes to call. John is spirited away to the well-hidden base of Knight Watch, the organization that stands between humanity and the real nasties the rest of the world doesn't know about. John and his reluctant teammates have to figure out who, or what, is pulling the strings before all of Knight Watch falls prey to a well-concealed puppetmaster."--